Assessment of Fascin by immunohistochemistry in colorectal carcinoma - H., Rajesh; Swaminathan, Rajendiran; Dennis Joseph, Leena; Srirangaramasamy, Jamuna; BS, Sangeetha (Tropical Journal of Pathology and Microbiology, 2019)
Background: The increased incidence of colon cancer may be attributed to an increase in the awareness of the disease, accessible screening modalities through widespread availability of preventive health check-ups & affordable newer imaging techniques. One of the essential components of clinical management of colon cancer is histopathological diagnosis and the role of Fascin-1 expression in colon cancers remains unexplored. This study was carried out to evaluate the fascin-1 expression in colon cancer specimens. Methods: This retrospective study was carried out on 60 paraffin blocks of colorectal carcinoma specimens received for a period of four years. IHC for Fascin was done on the sections along with controls. Clinical data regarding the participant’s demographics and medical history were captured from the hospital medical records. Gross findings were recorded from the blocks. Blocks with section containing normal epithelium and tumour were chosen for immunohistochemistry. Results: There was a significant association between pT1/pT2 staging and grade 0 fascin expression (80%) compared to those with pT3/pT4 staging (50%) (p<0.05). Similarly, grade 1 had strong positive correlation with fascin expression (70%) compared to other grades of the tumor (p<0.05). Conclusion: Presence of fascin expression significantly indicates the metastatic potential of colon carcinomas. Further research is required to delineate the mechanism of fascin expression at the cellular level in determining the prognosis of colon cancers.